PENGARUH PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR IPS SISWA DI KELAS V SDN 01 BANDAR BUAT PADANG - Silfi Melindawati (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study is almed to know the influence of the application of Cooperative Model Numbered Head Together (NHT) Type through/toward the IPS Students’ Achievement at Grade V at SDN 01 Bandar Buat Padang.This study is designed in Quasi Experimental Design with Posttest Only Controlled Design. Popullation in this study is two classess of students at Grade V at SDN 01 Bandar Buat Padang with 63 people totally. The sampling technique is total sampling which is derived to all popullation, so that VA class as experimental class and VB class as controlled class. Data collection in this study is by collecting the students’ test result in from of multiple choice test with 12 items of question. Data collected is analyzed with T-test instrument and show Tcounted = 2,425 and Ttable = 1,670 with db = 61 (n1+n2-2 = 32+31-2 = 61), where as Tcounted is bigger than Ttable so that H0 is refused and H1 is accepted. It could be concluded that Cooperative Model Numbered Head Together (NHT) type shared a significant influence toward V the IPS Students’ Achievement at Grade V at SDN 01 Bandar Buat Padang at academic year 2017/2018. Keywords: Cooperative Model Numbered Head Together (NHT) Type, Student Achievement, IPS